REFORM OF THE RESIDENTIAL CARE IN LITHUANIA FROM THE PERSPECTIVE OF INSTITUTIONAL THEORY - GENIENĖ, Rasa; ŠUMSKIENĖ, Eglė (Socialinė teorija, empirija, politika ir praktika, 2016)
Lithuania is currently undergoing a reform of the residential care, which is a major challenge for the system of care for persons with disabilities. This system has been formed during the Soviet times and still functions despite criticism for human rights violations and irrational use of financial resources. Currently this is the the only available form of care for persons with intellectual and/or psychosocial disabilities who are in need of a long-term care.Authors of the article employ the institutional theory and analyse resistance of the system to the reform. They conclude that social care organisations aim to keep the existing power and invoke financial, human and technical resources as well as the conjunctive relations. Authors also notice the vicious circle of the institutional functioning, while the necessity to isolate persons with disabilities is justified by lack of their self-support as well as lack of tolerance in the society. In the meantime, the institutions themselves exclude persons with disabilities and reduce their authonomy.
Keywords: Institutional Theory; Deinstitutionalization; Reform; Social Care